Alpha-tomatine activates cell cycle checkpoints in the absence of DNA damage in human leukemic MOLT-4 cells - Kúdelová, Jana; Seifrtová, Martina; Suchá, Lenka; Tomšík, Pavel; Havelek, Radim; Řezáčová, Martina (Journal of Applied Biomedicine, 2013)
Alpha-tomatine is a major glycoalkaloid found in the roots, leaves, stems and fruit of tomatoes Lycopersicon esculentum . Recently, alpha-tomatine has been recognized as a potential anticancer drug. In the present study, we identified the signaling cascades involved in the antitumor effect of alpha-tomatine on MOLT-4 leukemic cells. Alpha-tomatine inhibited the proliferation and decreased the viability of MOLT-4 cells in a dose-dependent manner. An increase in the activity of caspases 9 and 3/7 was not observed. However, an increase in the amount of p53 and its phosphorylation on serine 15, as well as an increased amount of mitochondrial protein PUMA was detected 4 and 24 h after exposure to alpha-tomatine at a concentration of 1–3 μmol/l. Inhibition of the proliferation of MOLT-4 cells by alpha-tomatine is also associated with an increase in p21 WAF1/CIP1 and the activation of Chk2. The comet assay did not detect significant amounts of single or double DNA strand breaks in cells treated with alpha-tomatine at concentrations of 0.1–9 μmol/l. Our results thus contribute to the understanding of the anticancer action of alpha-tomatine.
Keywords: nádorové buněčné linie; Comet Assay; statistika jako téma; Tumor Suppressor Protein p53; protein-serin-threoninkinasy; techniky in vitro; replikace DNA; Blotting, Western; checkpoint kinase 2; In Vitro Techniques; proliferace buněk; Cell Proliferation; poškození DNA; chk2; Cell Line, Tumor; nádorový supresorový protein p53; western blotting; DNA Replication; Tomatine; kometový test; Leukemia, T-Cell; průtoková cytometrie; leukemie T-buněčná; DNA Damage; Antineoplastic Agents; Protein Serine-Threonine Kinases; Statistics as Topic; onkogenní protein p21(ras); Oncogene Protein p21(ras); buněčná smrt; Flow Cytometry; Cell Death; tomatin; protinádorové látky; apoptóza; Puma; Apoptosis